Remittances, development level, and long-run economic growth - Kristina Matuzeviciute; Mindaugas Butkus (Economies, 2016)
This paper seeks to enrich the field of research on the topic of the impact of remittances on long-run economic growth. Using an unbalanced panel data covering a sample of 116 countries with different development levels over the period 1990-2014, we studied the interaction between remittances and the level of economic development, as well as its impact on long-run economic growth-because the impact of remittances could be influenced by the development level of the receiving countries. In parallel, we explored the hypothesis about diminishing a country's capacity to use remittances for promoting long-run economic growth as the abundance of remittances increases. To control the endogeneity while estimating the impact of remittances on long-run economic growth, we used OLS (ordinary least squares) with FD (first differences) transformation and FE (fixed effects) approaches and other controls of long-run growth. Our results showed that in general remittances have a positive impact on long-run economic growth, but the impact differs based on the country's economic development level and the abundance of remittances in the economy.
Keywords: F24; F43; O11; 330; remittances; long-run economic growth; development level